ESTROGEN RECEPTORS OF HAIRS BLACKS AND WHITES - Laswati, Hening; Pangkahila, Jahja Alex (BALI MEDICAL JOURNAL; Vol 3 No 3 (2014), 2014)
Background: Aging is termed as same as degenerative process, in which all part of tissue organs  retarted the microstructure either macrostructure, forming and function even the colour, including  black hair change to white hair. Several researchers have been recommended that estrogen hormone  be able ease black to white hair, but hormone without any presenting of receptor won’t be work  properly. The main aim of this study were to determine amount of estrogen receptor contents in  famales and males black and white hairs included the microscopically structure. Method: Twelve  females and males there were 50 -56 years old each pairs black and white head hairs were plucked  along with follicles. This estrogen receptors analyzed using radioreceptor binding assay there were  5mm eah hair follices including the root cutted and each pair put its in 2 ml glass tube already filled in  with 500 µl 125 I-estradiol and incubated in 37 o C for 3 hrs. Following times were over the tube flushed  twice carefully the hair won’t be flushed. Then count by putting in the gamma counter chamber for 1  minute each. The values that shown in the monitor as CPM (count per minute), recorded as receptor  of estradiol. Results: Mean (±SD) sum estrogen receptor in females black and white hairs were 479.3  ± 37.5 and 387.7 ± 33.0, but significantly decreased in male black hair was 316.9±17.8 and 274.0 ±  19.8. All those pairs significantly different either female black and white hairs or male black and white  hair and also significantly different among groups. Conclusion: The lowest estrogen receptors  recorded in male white hairs and microstructure decreasing of melanin contents.
Keywords: estrogen receptor; black; white hairs; microstructure